2008
DOI: 10.1002/jcb.21901
|View full text |Cite
|
Sign up to set email alerts
|

Migratory activity of human breast cancer cells is modulated by differential expression of xanthine oxidoreductase

Abstract: Xanthine oxidoreductase (XOR) may exert an important, but poorly defined, role in the pathogenesis of breast cancer (BC). Loss of XOR expression was linked to aggressive BC, and recent clinical observations have suggested that decreasing XOR may be functionally linked to BC aggressiveness. The goal of the present investigation was to determine whether the decreased XOR observed in clinically aggressive BC was an intrinsic property of highly invasive mammary epithelial cells (MEC). Expression of XOR was investi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
52
0

Year Published

2009
2009
2019
2019

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 38 publications
(57 citation statements)
references
References 74 publications
4
52
0
Order By: Relevance
“…First, to determine whether XOR overexpression would block IL-4 induced SUMO-PPAR␥, RAW264.7 cells were transfected with pCMV-Myc-XOR at various doses of input DNA. pCMV-Myc-XOR is a cDNA expression vector containing a functional XOR cDNA that is expressed under the control of the CMV constitutive promoter and produces ectopic overexpression of XOR (54). We observed that ectopic overexpression of XOR dose-dependently reduced levels of SUMO-PPAR␥ in IL-4-treated RAW264.7 cells (Fig.…”
Section: Xor Inhibitors Increase Levels Of Sumo-ppar␥ In Cultured Myementioning
confidence: 74%
“…First, to determine whether XOR overexpression would block IL-4 induced SUMO-PPAR␥, RAW264.7 cells were transfected with pCMV-Myc-XOR at various doses of input DNA. pCMV-Myc-XOR is a cDNA expression vector containing a functional XOR cDNA that is expressed under the control of the CMV constitutive promoter and produces ectopic overexpression of XOR (54). We observed that ectopic overexpression of XOR dose-dependently reduced levels of SUMO-PPAR␥ in IL-4-treated RAW264.7 cells (Fig.…”
Section: Xor Inhibitors Increase Levels Of Sumo-ppar␥ In Cultured Myementioning
confidence: 74%
“…Estrogen has been reported to decrease both protein levels and enzyme activity of xanthine dehydrogenase/xanthine oxidase (XDH/XO) in MCF-7 cells (Taibi et al, 2008). Loss of XO activity has been linked to aggressive breast cancer growth both in vivo and in vitro (Fini et al, 2008). The phenotypic significance is unclear but offers an intriguing hypothesis that would require further exploration with an approach tailored to this goal.…”
Section: Discussionmentioning
confidence: 99%
“…Apparently opposite effects of ROS have been observed. For example, in some cancer cells overproduction of endogenous ROS inhibits migratory activity, whereas depletion of ROS by introducing antioxidants or antioxidant enzymes to the cells stimulates migration (Fini et al, 2008;Shim et al, 2006). Clearly, additional studies are needed to resolve this contradiction and to further determine the mechanisms by which ROS affect cancer cell migration and invasion.…”
Section: Introductionmentioning
confidence: 99%